Gender Responsive Budget (GRB) Initiatives in Nepal: Achievements and Challenges - Rajkarnikar, Rashmi Shilpakar (International Journal of Bio-resource and Stress Management, 2019)
Gender responsive budgeting (GRB) aims at raising awareness of the gendered impacts of budget and to make governments accountable for ensuring gender equality and women’s rights. Government of Nepal has introduced gender budgeting system in 2007/08 for direct, indirect and neutral benefit to women. This paper examines the effectiveness of GRB implementation at local level. The descriptive technique is used to explain the gender sensitivity of policies, planning and programming and budgeting process of the selected five municipalities in Kathmandu Valley. The analytical technique is used to assess implementation and impacts of gender-focused policy, strategy and plan. The effectiveness of GRB is measured using two models: Integrated Organizational Model (IOM) and CAMELS rating. The results clearly show that mere preparing GRB and strategies does not solve the problem of inequality. Therefore, translating gender mainstreaming into actual action requires re-examination of the policies, programs and planning/budgeting process from a gender perspective. Analysis also shows that due to lack of gender need analysis before planning and allocating gender budget, implementation of GRB program are fully dependent on service provider’s strength, interest and capacity to implement women development programs. This has encouraged a kind of ad-hoc system which did not guarantee the immediate benefit to the participants in terms of income generation and employment creation.